Communications Trend Radar 2023. State revival, scarcity management, unimagination, augmented workflows & parallel worlds - Ansgar Zerfaß; Stefan Stieglitz; Sünje Clausen; Daniel Ziegele; Karen Berger (Academic Society for Management & Communication, 2023)
How do social changes, new technologies or new management trends affect communication work? A team of researchers at Leipzig University and the University of Potsdam (Germany) observed new developments in related disciplines. As a result, the five most important trends for corporate communications are identified annually and published in the Communications Trend Radar. Thus, Communications managers can identify challenges and opportunities at an early stage, take a position, address issues and make decisions. For 2023, the Communications Trend Radar identifies five key trends for corporate communications: State Revival, Scarcity Management, Unimagination, Parallel Worlds, Augemented Workflows.
Keywords: 650; public relation; trend; country; stakeholders; bottleneck; resilience; artificial intelligence; virtual reality; Öffentlichkeitsarbeit; Trend; Staat; Stakeholder; Engpass; Resilienz; Künstliche Intelligenz; Virtuelle Realität